2020
DOI: 10.3390/life10110290
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies of Primary HPV Testing Currently Applied for Cervical Cancer Screening

Abstract: The human papillomavirus is one of the most common sexually transmitted viruses, and an infection from this virus may become persistent, leading to diseases such as cervical cancer. In the past, cytology-based methods such as the Papanicolaou (Pap) test were imperative to identify the disease at a stage where it can be treated. However, since the 1980s where the etiological association of HPV and cervical cancer was identified, new tests began emerging directed towards identifying the virus. Furthermore, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 72 publications
1
39
1
8
Order By: Relevance
“…These tests have a high inter-observer variability (34-94% sensitivity) as their main limitation [2]. More recently, these tests have been replaced by PCR-based assays for the presence of hrHPV in a number of high-income countries [3]. While having an excellent negative predictive value, these assays lack specificity resulting in unnecessary referrals to a gynecologist and overtreatment (Figure 1).…”
Section: Population Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests have a high inter-observer variability (34-94% sensitivity) as their main limitation [2]. More recently, these tests have been replaced by PCR-based assays for the presence of hrHPV in a number of high-income countries [3]. While having an excellent negative predictive value, these assays lack specificity resulting in unnecessary referrals to a gynecologist and overtreatment (Figure 1).…”
Section: Population Screeningmentioning
confidence: 99%
“…A large number of tests has been developed (ca. 250 tests and more than 450 variants thereof) [29], but only a limited number has been validated [30] and approved for routine screening [3]. These tests may be divided according to the target into (i) viral DNA-and (ii) E6/E7 mRNA-based tests [31].…”
Section: Hrhpv Dna and Mrna Assaysmentioning
confidence: 99%
“…There are over 200 types of HPV with 14 strains considered to be associated with cervical cancer [13]. Nearly 80 million people in the United States have been infected with most clearing the infection without incident [14].…”
Section: The Evolution Of Hpv and Typesmentioning
confidence: 99%
“…Patient navigators to increase the vaccination rates and found that white patients are less likely to initiate the HPV vaccine than other ethnicities, however once initiated they were more likely to finish the series [22]. Rural parents were much less likely to encourage HPV vaccines as compared to their urban counterparts [13]. Women in the U.S. in general are basically poorly informed about HPV overall and found therefore, that provider education should target Non-Hispanic Blacks, lower level educated women, and those younger than 65 years of age.…”
Section: Vaccine Hesitancymentioning
confidence: 99%
“…Advances in diagnostic techniques, in particular, the development of easy-to-use molecular genetic tests, are replacing the use of the consolidated Pap test as a screening tool. HPV testing, using HPV DNA from exfoliated cervical cells, has been proposed based on the evidence of the role of "high-risk" types of HPV (especially HPV- 16, 18, 31, 33, 45, 51, 52, and 56) as the etiological agent of cervical cancer [163]. A significant increase in the validity of the available techniques allowed to demonstrate the presence of "highrisk" HPV in a high percentage of both invasive cancers and H-SIL, while the prevalence was low in the healthy population and moderate in L-SIL [164].…”
Section: Specimen Adequacymentioning
confidence: 99%